2020
DOI: 10.1007/s42947-020-6007-4
|View full text |Cite
|
Sign up to set email alerts
|

Sensor-based pavement diagnostic using acoustic signature for moduli estimation

Abstract: The diffusion of smart infrastructures for smart cities provides new opportunities for the improvement of both road infrastructure monitoring and maintenance management.Often pavement management is based on the periodic assessment of the elastic modulus of the bound layers (i.e., asphalt concrete layers) by means of traditional systems, such as Ground Penetrating Radar (GPR) and Falling Weight Deflectometer (FWD). Even if these methods are reliable, well-known, and widespread, they are quite complex, expensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
(31 reference statements)
0
13
0
2
Order By: Relevance
“…Instead of using back-calculating techniques, some works investigated the possibility of estimating the elastic modulus by finding correlations between other characteristics of the pavement and the pavement modulus. Here, Cafiso et al [45] demonstrated that extracted features from the vibro-acoustic signature of the pavement can have a good correlation with the pavement's elastic modulus.…”
Section: Estimation Of Pavement Characteristics and Prediction Of Mechanical Responsementioning
confidence: 91%
See 2 more Smart Citations
“…Instead of using back-calculating techniques, some works investigated the possibility of estimating the elastic modulus by finding correlations between other characteristics of the pavement and the pavement modulus. Here, Cafiso et al [45] demonstrated that extracted features from the vibro-acoustic signature of the pavement can have a good correlation with the pavement's elastic modulus.…”
Section: Estimation Of Pavement Characteristics and Prediction Of Mechanical Responsementioning
confidence: 91%
“…The self-powered wireless surface sensing approach made use of piezoelectric transducers to detect bottom-up cracking. Another work that explored a method for detection of cracks inside the pavement was developed by Fedele et al [42] and Cafiso et al [45], which resorted to microphones placed on the pavement surface to record its vibro-acoustic signature. Since the propagation of both vibration and sound is, among others, a function of the proprieties of the material, this method is based on the hypothesis that, in the presence of cracks, the stiffness of the pavement decreases, resulting in a reduction in the wave transmission capacity of the material.…”
Section: Embedded Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, based on previous studies, 45 a given variation of the features listed above can be associated with the presence of a crack or a defect of the road.…”
Section: Smart Sensors and Innovative Equipmentmentioning
confidence: 95%
“…In [ 36 ], horizontal strains are used to calculate the pavement moduli. Cafiso et al [ 37 ] used a pre-polarized, omnidirectional, acoustically isolated microphone to collect the vibro-acoustic signatures of road pavements and correlate them to the elastic moduli obtained from FWD. The proposed solution could be used to continuously monitor the downgrading of asphalt road pavements under traffic.…”
Section: Introductionmentioning
confidence: 99%